Specific Immune Intervention with Monoclonal Antibodies for the Treatment of Multiple Sclerosis - Trebst, Corinna; Voß, Elke; Skripuletz, Thomas; Stangel, Martin (Current Medicinal Chemistry, 2010)
Multiple sclerosis (MS) is considered to be an autoimmune disease leading to inflammatory demyelination and axonal damage in the central nervous system (CNS). Current treatments involve non-specific immunosuppression and immunomodulation. The development of monoclonal antibodies for therapeutic use allows targeting of specific immune mechanisms. Natalizumab, a monoclonal antibody directed against α4β1 integrin that plays a crucial role in the transmigration of immune cells across the blood-brain-barrier, has been licensed for relapsing-remitting (RR) MS in 2006. Rituximab, directed against CD20 expressed on pre B-cells and B-cells has been tested successfully in a phase II trial and suggests that several B-cell dependent mechanisms may be relevant to the mode of action. Alemtuzumab, targeting CD52 expressed on T-cells, B-cells, monocytes and macrophages, has also shown to be effective in early RRMS and phase III trials are currently ongoing. Daclizumab binds to CD25, the alpha chain of the interleukin (IL)-2 receptor, and is also being tested for RRMS. Beside the clinical data the results from these clinical trials give also new insights into the pathogenesis of MS. We critically discuss the potential but also the pitfalls and potential hazards of these new therapeutic strategies.
Keywords: multiple sclerosis